Transportation quality indices for economic analysis of non-metropolitan cities - Vachal, Kimberly; Bitzan, John; Button, Kenneth (European Journal of Transport and Infrastructure Research, 2007)
It is generally agreed that transportation plays a role in economic development, but it often is assumed away in empirical work due to data voids or under implicit assumptions that it is largely an inert factor. This paper seeks to add to the quantitative material by offering estimates of the relative quality of surface freight transportation service resources available to non-metropolitan cities across the US. Indicators suggest that cities located in the Midwest have relatively higher freight transport service quality, and that a cluster of north-eastern states are at a disadvantage, considering the quality of freight service for non-metropolitan areas. Transportation quality indicators developed in this research offer a new opportunity to consider transportation in analysis of economic development policies and strategies.